QUANTITATIVE ESTIMATION OF EXPONENTS OF POWER-LAW FLOW WITH CONFIDENCE INTERVALS IN DUCTILE SHEAR ZONES - Mulchrone K.F. (My University, 2001)
Talbot (Journal of Structural Geology 21, 1535-1551, 1999b) introduced a new model for ductile shear zones as counterflow boundaries in pseudoplastic power-law fluids, and demonstrated that natural shear zones empirically fit theoretical curves generated by his model. Thus estimates of the power-law exponent relating stress and strain are deduced. It is shown here how application of standard non-linear statistical techniques to shear zone displacement data allows quantitative estimation of the power-law exponent together with confidence intervals of the calculated value. Application to natural shear zones verifies the method and also validates the applicability of the model. It is hoped that this will encourage field geologists to apply the model of Talbot to natural examples. Thereby a database of power-law exponents for a wide variety of lithologies and metamorphic grades may be assembled.